Interactive Graphic Representation of Railway Systems - Amza, Mona Diana (My University, 2010)
This paper presents a study of available technologies which could be employed for the development of graphical representations of supervised railways. Expected technical and non-technical characteristics are identified and analysed in three frameworks, Adobe Flex, Microsoft Silverlight and JavaFX. Their advantages and drawbacks are discussed, and the technology proposed is Adobe Flex. The solution is then implemented in a prototype, representing a proof of concept which can further be used as starting point and reference for future projects.
Keywords: Datorteknik; Computer Engineering